Impact of the Omnibus Law/Job Creation Act in Indonesia - Harahap, Hadry; Sihombing, B. F.; Hamid, Adnan (International Journal of Scientific Research and Management (IJSRM), 2020)
The purpose of this research is to analyze the impact of the Omnibus Law/Job Creation Act related to the discussion process and post-endorsement by the legislature, the House of Representatives of the Republic of Indonesia. This research uses the normative juridical method, which is a legal research conducted by examining library materials. or secondary data and carried out with descriptions, measurements and accurate reporting of the characteristics of some of the phenomena under study. The findings of this study are that the government and legislature in the process and discussion tend to conflict with the 1945 Constitution article 1 paragraph (3), article 27 paragraph (1), and article 28 paragraph (5) and Law No.12 of 2011. regarding the Formation of Legislative Regulations as updated by Law No.15 of 2019 . Pancasila as a philosophische grondslag is stated in the Preamble of the 1945 Indonesian Constitution which means that Pancasila is positioned as a source of constitutional law in Indonesia, is an inspiration for the formation of the rule of law in Indonesia.  As a result, civil society organizations oppose and reject this regulation so that it is hoped that President Joko Widodo can issue a Government Regulation in Lieu of Law.